Long-Term Relationship between Inflation and Public Sector Deficit in the Turkish Economy and its Macroeconomic Implications (1975-2014) - Gökçe, Atilla; Ãakmak, Umut (Journal of Economics and Behavioral Studies, 2016)
The process of deterioration in the fundamentals, in particular those related to inflation and the public sector deficits, that had started in the 1980’s have accelerated in the 1990’s. Meanwhile two way causative relations seem to have appeared between the fluctuations of some fundamentals. In this context, this paper examines the long term relationship between inflation and the public sector deficit and provides an analysis of the macro dynamics that derive from this relationship. Following a summary of the theoretical literature on the relationship between inflation and the public sector deficit, the behavior of these two variables in the 1975-2014 periods are delineated and an analysis of their relationship to some selected macro-variables is presented. The most important result of this article is that high and chronic inflation rates are one of the responsible of deterioration which appeared on the main economic variables particularly in the public sector balance. Similarly, in the 2000â€™s, on the basis of positive developments in the public balance lies in falling inflation rates quickly and permanently.